1992
DOI: 10.1073/pnas.89.14.6580
|View full text |Cite
|
Sign up to set email alerts
|

Active nuclear import of human immunodeficiency virus type 1 preintegration complexes.

Abstract: After cell infection by the human immuno deficiency virus type 1 (HIV-1), nascent viral DNA in the form of a high molecular weight nucleoprotein preintegration comin plex must be transported to the nucleus of the host cell prior to integration of viral DNA with the host genome. The mechm used by retroviruses for nuclear targeting of preintegration complexes and dependence on cell division has not been established. Our studies show that, after infection, the preintegration complex of HIV-1 was rapidly transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
423
2
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(435 citation statements)
references
References 19 publications
(8 reference statements)
8
423
2
2
Order By: Relevance
“…10,27,28 Similar NLS-mediated nuclear import models have been proposed for viral genomes, including HIV and adenovirus. 29,30 In addition, several groups have shown that by complexing plasmids with proteins, such as histone proteins and nuclear factor kB, or with peptide nucleic acids (PNAs) that contain nuclear localization signals, nuclear import and expression are enhanced. [31][32][33][34] As SRF and NK3 factors are coexpressed specifically in SMCs, other cell types are unable to form an import complex on the pDNA, making the SMGA promoter a tissuespecific DTS.…”
Section: Discussionmentioning
confidence: 99%
“…10,27,28 Similar NLS-mediated nuclear import models have been proposed for viral genomes, including HIV and adenovirus. 29,30 In addition, several groups have shown that by complexing plasmids with proteins, such as histone proteins and nuclear factor kB, or with peptide nucleic acids (PNAs) that contain nuclear localization signals, nuclear import and expression are enhanced. [31][32][33][34] As SRF and NK3 factors are coexpressed specifically in SMCs, other cell types are unable to form an import complex on the pDNA, making the SMGA promoter a tissuespecific DTS.…”
Section: Discussionmentioning
confidence: 99%
“…PIC is transported through nuclear pores via an active, energydependent mechanism (Bukrinsky et al, 1992;Depienne et al, 2001;Gallay et al, 1997).…”
Section: Nuclear Importmentioning
confidence: 99%
“…[1][2][3][4] Lentiviral vectors have the unique feature of being able to transduce nondividing cells, making it particularly attractive for certain gene therapy applications. [5][6][7] Sometimes, to achieve a desirable therapeutic effect, the viral vectors must be capable of precisely delivering a gene of interest to specific cells without influencing non-target cells. [8][9][10] Many efforts have been made to develop such targeting viral vector systems mostly by altering the viral envelope glycoprotein.…”
Section: Introductionmentioning
confidence: 99%